Adsorptive Removal of Metanyl Yellow on Mesoporous Nickel Aluminophosphate Molecular Sieves from Aqueous Solution - Kannan, C.; Muthuraja, K.; Devi, M.R. (Asian Journal of Chemistry, 2012)
Metanyl yellow, an anionic dye, toxic to the environment by polluting the water bodies has removed from aqueous solution through adsorption method over mesoporous nickel aluminophosphate (Ni-AlPO4). Attempts have been made through batch removal of the dye and the adsorbent has been found to exhibit good efficiency to adsorb metanyl yellow. Under batch technique, the effect of contact time, temperature, concentration and dosage of adsorbent have been studied to find out the maximum uptake of dye on adsorbent. The dye uptake on the adsorbent is found to follow Langmuir and Freundlich adsorption isotherms models and a second order rate kinetics. Adsorption of metanyl yellow on Ni-AlPO4 is influenced by the temperature. The adsorption thermodynamic parameters, namely DHº, DGº and DSº, have determined for the adsorption. The DHº value proved that the adsorption process is endothermic. The positive DSº value indicates that entropy is a driving force for the adsorption. The negative DGº value shows the adsorption process is spontaneous.